Youth Perception Of Sexual Behavior In Islamic Religious Context SMAN 61 Jakarta - Wartini, Tini; Wahyuningsih, Sri Atun; Isnayati (Jurnal Life Birth, 2020)
In the current era of globalization, there is a fast flow of information, which can affect the structure of society including the attitudes and behavior of adolescents, including free sexual behavior among adolescents. The purpose of this study is to determine the relationship between teenagers' perceptions of sexual behavior in the context of Islam. This research method is descriptive, a population of 4198 adolescents, a sample of 98 adolescents, data collection techniques using a questionnaire, data analysis using a Likert scale. Overall results of this study obtained results from the majority of respondents (57.14%) support (favorable) sexual behavior in the context of the Islamic religion. Judging from the aspect of sexual acts, most of the respondents (55.10%) supported (favorable) sexual behavior in the context of the Islamic religion. From the aspect of sexual communication, it was found that most of the respondents (58.16%) supported (favorable) sexual behavior In the context of Islam, and from the aspect of physical sexual appearance, it was found that most respondents (52.04%) supported (favorable) sexual behavior in the context of Islam. Conclusion In adolescents who do not support each other (Unfavorable) sexual acts in Islam, generally they know in line with Islamic rules regarding sexual acts for adolescents, but because of the lack of filling in their faith, their commitment to Islamic rules is not strong so that their perceptions tend to be less consistent. Due to this, a permissive (awry) attitude emerged from the teenagers. If there is an opportunity for teenagers to have physical touch, hold meetings to make out, sometimes the teenagers are looking for opportunities to have sexual intercourse.